Economics of Cropping Patterns of Farms in Palawan, Philippines - Rodriguez Cacatian, Evelyn (1988)
This study was conducted to further the understanding on the cropping patterns practiced in Palawan, Philippines. Based on the concept that the farm and the farm household are interrelated and using various analytical techniques, the current cropping patterns, the availability and the efficiency of resource utilization were analysed and documented. Farm house holdsin the study are a were basically subsistence in nature since their gross income (cash and imputed) barely met the production and personal consumption needs of the farm household. However, they were observed to exhibit a considerable degree of market orientation in both input utilization and production. Fertilizer and hired labour constitute a greater proportion of the operating cost.Sales of annual crops constitute a greater proportion of the cash income and it was augmented with income from non-farm activities.